2018
DOI: 10.1080/17450101.2018.1468592
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of social protection and mobilities: a move towards a ‘Practical Utopia’ research agenda

Abstract: Currently, a number of contributions in mobility studies are looking for fruitful intersections with other 'adjacent' approaches . In this spirit, our theoretical paper argues to study one particular aspect: the intersection of social protection and mobilities. Currently, the provision of social services in the 'West' is strongly entrenched within nation-state logics, which assume that clients' immobility is a precondition of service delivery and that national citizenship is the desirable conditionality of gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 78 publications
0
18
0
1
Order By: Relevance
“…They have demonstrated that related processes of bordering are interwoven and thus invisibilized and naturalized in the everyday life of all kinds of people (and not just of "migrants") and that these processes impact on the subjectivities of "citizens" and "aliens" alike (Anderson 2015: 185;Mezzadra and Neilson 2013). Besides providing substantial findings on the governance and construction of "Roma beggars" in an Austrian city, I therefore argue that this paper demonstrates the richness of an empirical and theoretical orientation which lies at the intersection of (im)mobilities and social (de)protection, amended by a No Borders perspective, to analyse critical issues commonly framed by other concepts and dealt with under "migration studies", "welfare studies" or "citizenship studies" (Raithelhuber et al 2018). An approach of this kind claims to liberate us from the alluring and somewhat misleading category of "migrants".…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…They have demonstrated that related processes of bordering are interwoven and thus invisibilized and naturalized in the everyday life of all kinds of people (and not just of "migrants") and that these processes impact on the subjectivities of "citizens" and "aliens" alike (Anderson 2015: 185;Mezzadra and Neilson 2013). Besides providing substantial findings on the governance and construction of "Roma beggars" in an Austrian city, I therefore argue that this paper demonstrates the richness of an empirical and theoretical orientation which lies at the intersection of (im)mobilities and social (de)protection, amended by a No Borders perspective, to analyse critical issues commonly framed by other concepts and dealt with under "migration studies", "welfare studies" or "citizenship studies" (Raithelhuber et al 2018). An approach of this kind claims to liberate us from the alluring and somewhat misleading category of "migrants".…”
Section: Discussionmentioning
confidence: 87%
“…My intention was to delve into a "random" empirical field to substantialize and develop conceptual and theoretical reflections on the intersections of social (de)protection and (im)mobilities, inspired by a No Borders approach. In a nutshell, I adopted a "mobilities" perspective that reflects a No Borders approach (Raithelhuber et al 2018).…”
Section: Methodology and Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As exclusive 'national' societies were being formed, the newly emerged nation-states began to regulate social mobilities of people within their territories, primarily through the creation of policies affecting people's access to education, employment, housing, welfare, health care, and so on. At the same time, nation-states began to restrict the mobilities of people moving across their borders (Raithelhuber et al 2018). As the international system of nation-states took shape, sovereign, territorially bounded nation-states formed and were solidified through the creation of nationalities and national identities.…”
Section: Historizing the Nation-statementioning
confidence: 99%
“…This paper draws upon the analytical and methodological toolkits offered by a mobilities approach along with the insights of No Borders Studies. A No Borders perspective asserts that people should not be sorted, labeled and categorized through inherently exclusionary state forms of identification such as 'migrant' and 'citizen' (Baines and Sharma 2002;Raithelhuber et al 2018). This paper applies sub-citizenship as a new theoretical lens to exploration how human life is organized within contemporary neoliberal processes.…”
mentioning
confidence: 99%